Strategy to Improve the use Of Village and Regional Information Systems (SIDEKA) In Cianjur District - Kusuma, Eka Chandra; Harianto, Harianto; Kolopaking, Lala M (JURNAL MANAJEMEN AGRIBISNIS; Vol 8 No 2 (2020): OCTOBER 2020DO - 10.24843/JMA.2020.v08.i02.p01, 2020)
ABSTRACT Funding and Human Resources (HR) can increase the successful use of Village and Regional Information Systems (SIDEKA). In this study, using Confirmatory Factor Analysis (CFA) on the factors that influence the successful implementation of SIDEKA in the District shows that funding of SIDEKA allocation, SIDEKA manager's human resource management and accompanying SIDEKA influence positively and significantly on the success of SIDEKA implementation. Several alternative strategies have been successfully formulated using the analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT) on internal and external factors. The priority strategy chosen based on respondents' assessment is the strategy of weaknesses and opportunities (WO) including first allocating and increasing SIDEKA funds. Second, collaborating on education and training for managers. And third, improvement of the Information and Communication network in Cianjur Regency